Measuring PT Adaro's Financial Resilience: Liquidity Analysis - Jusnia, Jusnia; Nazwa Gani F. Komile; Ashar Muhammad (Amsir Accounting & Finance Journal, 2026)
This study aims to analyze the liquidity performance of PT Adaro Energy Indonesia Tbk during the 2020-2024 period. The method employed is financial ratio analysis, focusing on the Current Ratio, Quick Ratio, and Cash Ratio derived from the company’s annual financial statements. The results indicate that PT Adaro maintains formidable financial resilience with a significant strengthening trend in liquidity, driven by effective working capital management and the capitalization of the global commodity price surge. A crucial finding of this research is the drastic spike in all liquidity ratios in 2024, with the Current Ratio reaching 403%. This phenomenon is identified as a direct impact of the substantial decrease in current liabilities following the corporate spin-off of the thermal coal business pillar. While the company’s cash position remains exceptionally secure with a Cash Ratio consistently above 100%. This study highlights the implications of excess liquidity. Consequently, the primary challenge for management lies in strategic capital allocation, whether through accelerating investments in the renewable energy sector or distributing value to shareholders, to maintain optimal capital structure efficiency.